THE HESYCHAST METHOD OF PRAYER - James Aerthayil (Journal of Dharma, 2020)
One of the many fascinating interests of contemporary times is the quest for God-experience. Traditionally, expressions like contemplation, God-experience etc., have been used for talking about the elite. This is being challenged now. Everybody has a right to God-experience and the consequent calm and peace of mind. To achieve this, the general tendency today is to avoid elaborate traditional methods involving ritualism, and pursue simple forms of prayer. Hence people everywhere have turned towards the Buddhists in Japan, the Hindu Yogis in India, and the monks of Mount Athos, in their search for experience and interiority. Zen, Yoga, T.M., Jesus Prayer etc., are no longer strange words to modern man. Irrespective of their religious affiliation, people positively affirm the therapeutic and spiritual value of these methods. In the past few decades, so much has been written about these methods. The Hesychast method of prayer of the Christian East has also gained considerable atten- tion. However what exactly is Hesychasm and Jesus Prayer, and what their relationship is, is not clear to many. Through an historical and theoretico-practical survey, we make an attempt to clarify some of their aspects in the following pages.